TAKE ME BACK TO MY INDIAN FIRE (Canadian Journal of Native Studies, 2026)
This article explores how food is connected to health, not only by thephysical body but through a connection to our culture, our community,our ancestors, and the earth. Establishing food security and sovereignty– access to traditional foods and control over food supply – is crucialto decolonization and healing for Indigenous people. This article combinesteachings from Elders with insights from an Indigenous chef abouthow food can heal. It takes the reader on a culinary journey through aheart-warming event “Community Kitchen: Food, Medicine and Memories”held by the First Nation House at the University of Toronto.